2011
DOI: 10.1152/jn.00746.2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TMS on visual motion sensitivity: an increase in neural noise or a decrease in signal strength?

Abstract: Ruzzoli M, Abrahamyan A, Clifford CW, Marzi CA, Miniussi C, Harris JA. The effect of TMS on visual motion sensitivity: an increase in neural noise or a decrease in signal strength? J Neurophysiol 106: 138-143, 2011. First published May 4, 2011 doi:10.1152/jn.00746.2010The underlying mechanisms of action of transcranial magnetic stimulation (TMS) are still a matter of debate. TMS may impair a subject's performance by increasing neural noise, suppressing the neural signal, or both. Here, we delivered a single pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Studies have emphasized interindividual variability in the neuromodulatory effects of rTMS as a function of the rTMS frequency applied (23). Furthermore, as the effects of TMS have been shown to be state-dependent (37), lpIPL may have responded differently to the two frequencies because of disparities in ongoing levels of tonic activation (38). In this light, the prerTMS activity could serve to partially determine the degree and direction of cortical excitability changes at pIPL as a way of maintaining a homeostatic level of cortical activation within a physiologically useful range (39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have emphasized interindividual variability in the neuromodulatory effects of rTMS as a function of the rTMS frequency applied (23). Furthermore, as the effects of TMS have been shown to be state-dependent (37), lpIPL may have responded differently to the two frequencies because of disparities in ongoing levels of tonic activation (38). In this light, the prerTMS activity could serve to partially determine the degree and direction of cortical excitability changes at pIPL as a way of maintaining a homeostatic level of cortical activation within a physiologically useful range (39).…”
Section: Discussionmentioning
confidence: 99%
“…No increase in false alarms was found for the nonbiological motion task, indicating that local biological motion information may trigger specific neural computations and/or populations and may even selectively engage the match-to-body process. Studies in which signal and noise are manipulated independently could help test these possibilities (Ruzzoli et al, 2011). Eye tracking can be used to test whether TMS affects how observers scan the noise-masked displays.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is in line with several studies that have argued that TMS acts by adding neural noise to the perceptual process rather than by affecting signal strength (Ruzzoli et al 2010;Schwarzkopf et al 2011). Nevertheless, two other studies argued for the opposite conclusion (Harris et al 2008;Ruzzoli et al 2011). This suggests that the precise influence of TMS may depend on the specific stimulation and task parameters.…”
Section: Does Tms Affect Noise or Mean Signal Intensity For Visual Pementioning
confidence: 98%
“…To ensure that subjects do not consciously adjust their criteria to compensate for the change in signal variability, ideally, the difference between the conditions of interest should be subtle and mainly focused on increasing variability in one of the conditions. Although transcranial magnetic stimulation (TMS) to the visual cortex is often used to completely "knock out" conscious perception (e.g., Boyer et al 2005;Breitmeyer et al 2004;Kastner et al 1998;Koivisto et al 2010Koivisto et al , 2011Ro et al 2004), some recent studies have shown that low-intensity stimulation can effectively inject noise to the visual system (Ruzzoli et al 2010;Schwarzkopf et al 2011; although, see Harris et al 2008;Ruzzoli et al 2011). In the present study, we applied single-pulse TMS at an intensity below the threshold for the conscious perception of phosphenes.…”
mentioning
confidence: 89%